PEMAKAIAN HUKUM ASING DALAM HUKUM PERDATA INTERNASIONAL: KEWAJIBAN DAN PELAKSANAANNYA DI PENGADILAN INDONESIA - Afifah Kusumadara (Arena Hukum)
This article is reviews the application of foreign law by Indonesian courts as governed by the Indonesian Private International Law (PIL). The review is based on Acts and regulations related to PIL, case-laws, and text-books on PIL. The result demonstrates that Indonesian judges often do not implement the principle of iura novit curia in the application of foreign law; ignore foreign elements in their cases; and keep applying Indonesian law even though the rules of Indonesian PIL lead to the foreign law. Therefore, the Bill of Indonesian PIL shall be passed and enacted soon so that there are no more excuses by Indonesian courts not to apply foreign law. Indonesian courts including the Supreme Court, should have a special unit within their system that can provide judges with information on and translation of foreign law. In addition, it is necessary to establish international cooperation regarding exchange of information on foreign law between Indonesia’s Supreme Court and other countries’ Supreme Courts.